Urokinase-type plasminogen activator (uPA) protects the tripartite synapse in the ischemic brain via ezrin-mediated formation of peripheral astrocytic processes. Issue 11 (November 2019) - Diaz, Ariel; Merino, Paola; Manrique, Luis G; Cheng, Lihong; Yepes, Manuel
Cerebral ischemia has a harmful effect on the synapse associated with neurological impairment. The "tripartite synapse" is assembled by the pre- and postsynaptic terminals, embraced by astrocytic elongations known as peripheral astrocytic processes (PAPs). Ischemic stroke induces the detachment of PAPs from the synapse, leading to synaptic dysfunction and neuronal death. Ezrin is a membrane-associated protein, required for the formation of PAPs, that links the cell surface to the actin cytoskeleton. Urokinase-type plasminogen activator (uPA) is a serine proteinase that upon binding to its receptor (uPAR) promotes neurite growth during development. In the adult brain, neurons release uPA and astrocytes recruit uPAR to the plasma membrane during the recovery phase from an ischemic stroke, and uPA/uPAR binding promotes functional improvement following an ischemic injury. We found that uPA induces the synthesis of ezrin in astrocytes, with the subsequent formation of PAPs that enter in direct contact with the synapse. Furthermore, either the release of neuronal uPA or intravenous treatment with recombinant uPA (ruPA) induces the formation of PAPs in the ischemic brain, and the interaction of these PAPs with the pre- and postsynaptic terminals protects the integrity of the "tripartite synapse" from the harmful effects of the ischemic injury.